The Cambridge companion to the writings of Julius Caesar - Grillo, Luca, 1970-; Krebs, Christopher B. (Cambridge : Cambridge University Press, 2018)
Well-known as a brilliant general and politician, Julius Caesar also played a fundamental role in the formation of the Latin literary language and remains a central figure in the history of Latin literature. With twenty-three chapters written by renowned scholars, this Companion provides an accessible introduction to Caesar as an intellectual along with a scholarly assessment of his multiple literary accomplishments and new insights into their literary value. The Commentarii and Caesar's lost works are presented in their historical and literary context. The various chapters explore their main features, the connection between literature, state religion and politics, Caesar's debt to previous Greek and Latin authors, and his legacy within and outside of Latin literature. The innovative volume will be of great value to all students and scholars of Latin literature and to those seeking a more rounded portrait of the achievements of Julius Caesar.
Introduction. Caesarian questions: then, now, hence / L. Grillo and C. Krebs -- Literature and politics. Caesar, literature and politics at the end of the Republic / K. Raaflaub -- The Commentarii in their propagandistic context / C. Krebs -- Caesar constructing Caesar / W. Batstone -- Priesthoods, gods and stars / J. Rüpke -- The politics of geography / A. Riggsby -- Nostri and'the other(s)' / A. Johnston -- Genre, rhetoric, language and style. Genres and generic contaminations in the Commentarii / D. Nousek -- Caesar's style / C. Krebs -- Speeches in the Commentarii / L. Grillo -- Wit and irony / A. Corbeill -- Literary approaches to Caesar / L. Grillo -- Fragmentary works. Caesar the linguist: the debate about the Latin language / G. Pezzini -- Caesar's orations / H. van der Blom -- Caesar's poetry in its context / Sergio Casali -- Anticato / A. Corbeill -- The letters of Caesar / R. Morello -- Sources and Nachleben. Caesar and Greek historians / L. Pitcher -- Caesar and Roman historiography prior to the Commentarii / M. Chassignet -- The Corpus Caesarianum / J. F. Gaertner -- Caesar in Livy and Tacitus / C. S. Kraus -- Caesar, Virgil and Lucan / T. Joseph -- Narrating the Gallic and Civil Wars with and beyond Caesar / J. Thorne -- Writing war with Caesar: the Commentarii's afterlife in military memoirs / H. Schadee.
Title from publisher's bibliographic system (viewed on 05 Jan 2018).
Keywords: Caesar, Julius -- Criticism and interpretation; Caesar, Julius -- Sources; Caesar, Julius -- Influence; Historiography -- Rome